Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

A model for the number of lobsters caught per year is based on the assumption that the number of lobsters caught in a year is the average of the number caught in the two previous years.

a) Find a recurrence relation for $L_n$, where $L_n$ is the number of lobsters caught in year n, under the assumption for this model.

My answer: $$L_n = \frac{1}{2}L_{n-1} + \frac{1}{2}L_{n-2}$$

b) Find $L_n$ if $100,000$ lobsters were caught in year $1$ and $300,000$ were caught in year $2$.

My Answer: The characteristic equation is $$r^2 - \frac{1}{2}r - \frac{1}{2} = 0$$ and $$\frac{1}{2}(2r+1)(r-1) = 0$$

The roots are $r=-\frac{1}{2}$ and $r=1$.

The general solution is $$L_n = k_1\left(-\frac{1}{2}\right)^n + k_2.$$

Considering the initial conditions, we have: $$-\frac{1}{2}k_1 + k_2 = 100000 \quad\mbox{and}\quad \frac{1}{4}k_1 + k_2 = 300000$$

Solving this system of equations, we have $$k_1 =\frac{800000}{3}$$ $$k_2 = \frac{700000}{3}$$ and

$$L_n = \frac{800000}{3}\left(-\frac{1}{2}\right)^n + \frac{700000}{3}.$$

Is this right? Thank you!

share|improve this question
    
I love lobster. Your typesetting, less... This could be useful in the future. –  1015 Apr 14 '13 at 22:21
1  
I tried to fix it..better? –  stevenmadden Apr 14 '13 at 22:28
    
Much better! I did the rest. So for instance 1/2 can be written \frac{1}{2}. –  1015 Apr 14 '13 at 22:32
2  
Regarding the proof, it looks good to me. –  1015 Apr 14 '13 at 22:34
add comment

1 Answer 1

OK, use generating functions (just for fun). The recurrence is: $$ L_{n + 2} = \frac{1}{2} (L_{n + 1} + L_n) \qquad L_1 = 100000, L_2 = 300000 $$ Define the generating function: $$ A(z) = \sum_{n \ge 1} L_n z^{n - 1} $$ By the properties of generating functions: $$ \frac{A(z) - L_1 - L_2 z}{z^2} = \frac{1}{2} \frac{A(z) - L_1}{z} + \frac{1}{2}A(z) $$ As partial fractions: $$ A(z) = \frac{700000}{3} \frac{1}{1 - z} - \frac{400000}{3} \frac{1}{1 + z / 2} $$ Expanding the geometric series: $$ L_n = \frac{700000}{3} - \frac{400000}{3} \left( - \frac{1}{2} \right)^{n - 1} = \frac{700000}{3} - \frac{800000}{3} \left( - \frac{1}{2} \right)^n $$

share|improve this answer
    
This is a little above my head..is my original answer incorrect? Thanks! –  stevenmadden Apr 14 '13 at 22:54
    
@jtm22, your solution is just fine. Simplified my last result to match yours. Upvoted your question because of it. –  vonbrand Apr 14 '13 at 22:59
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.